Enhancement of Brillouin Stokes generation in the S-band region using a combination S-band Depressed Cladding Erbium Doped Fiber and Semiconductor Optical Amplifier - Ahmad, Harith; Zulkifli, Mohd Zamani; Hassan, Nor Ahya; Harun, Sulaiman Wadi (IOP Publishing, 2012)
A hybrid Depressed-Cladding Erbium Doped Fiber (DC-EDF) together with a broadband Semiconductor Optical Amplifier (SOA) to enhance the generation of Stokes and anti-Stokes in a 7.7 km long Dispersion Compensating Fiber (DCF) is proposed and demonstrated. The performance of the proposed system is compared against that of a conventional system with only the DC-EDF as the gain medium, and the incorporation of the SOA can be seen to enhance the generation of Brillouin Stokes significantly. The proposed system is able to generate an output comb with a flat-top and more than 29 Stokes and 13 anti-Stokes lines, an increase of 14 and 8 lines respectively over the conventional system and covering the entire S-band region. The output comb generated is highly stable over time.